2015
DOI: 10.1021/am509142k
|View full text |Cite
|
Sign up to set email alerts
|

Light-Enhanced Bacterial Killing and Wash-Free Imaging Based on AIE Fluorogen

Abstract: The rapid acquisition of antibiotic resistance poses difficulties in the development of effective methods to eliminate pathogenic bacteria. New bactericides, especially those do not induce the emergence of resistance, are thus in great demand. In this work, we report an aggregation-induced emission fluorogen, TPE-Bac, for bacterial imaging and elimination. TPE-Bac can be readily dissolved in aqueous solution with weak emission. The presence of bacteria can turn on its emission, and thus no washing step is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 36 publications
(59 reference statements)
1
85
0
Order By: Relevance
“…Motivated by the initial success, we and others have further developed AIE probes to detect and kill bacteria . These probes generally light‐up in response to bacteria, so that the detection can be done in real time without washing steps . Some of these probes also showed obvious dark toxicity, which can be combined with light‐induced photosensitization to effectively kill bacteria even under sunlight .…”
Section: Methodsmentioning
confidence: 87%
“…Motivated by the initial success, we and others have further developed AIE probes to detect and kill bacteria . These probes generally light‐up in response to bacteria, so that the detection can be done in real time without washing steps . Some of these probes also showed obvious dark toxicity, which can be combined with light‐induced photosensitization to effectively kill bacteria even under sunlight .…”
Section: Methodsmentioning
confidence: 87%
“…Through systematic studies, restriction of intramolecular motion (RIM) was identified as the main cause for the AIE effect . These AIE luminogens (AIEgens) show great potential in biological research, and lots of biological applications have been developed with these materials, including cell and bacteria imaging, tissue and tumor visualization, therapy, and drug delivery . The fluorescence turn‐on characteristics of the AIEgens upon binding to the targets make them excellent candidates as fluorescence sensors and inspire us to explore their potentials in bacterial susceptibility evaluation and antibiotics screening.…”
Section: Methodsmentioning
confidence: 99%
“…A new AIEgen 4 was synthesized following the procedures reported previously (Scheme S2, Supporting Information) . The cross McMurry coupling reaction of 4‐hydroxybenzophenone and 4‐bromobenzophenone gave 1 , which then underwent Williamson ether synthesis reaction by treatment of 1‐bromoundecane to form 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between the aggregation process and morphologies of aggregates in different solvents is of elemental importance . “AIEgens” for imaging of bacteria and photodynamic killing have been reported by Tang et al . They have also been used for the generation of metal nanoparticles ,.…”
Section: Introductionmentioning
confidence: 96%